Machiavellianism, Profit, and the Dimensions of Ethical Judgment: A Study of Impact - Schepers, Donald H. (Journal of business ethics, 2003)
Research by Reidenbach and Robin (1990) provides a means to study the differential impact of three dimensions of attitude toward ethics: moral equity, relativism, and contractualism. It is hypothesized that moral equity will be the most significant predictor of ethical judgment and intent to act. It is also hypothesized that Machiavellianism and profit will affect relativism and contractualism dimensions, but not moral equity. Additionally, it is hypothesized that Machiavellianism will interact with profit to affect intent to act. Moral equity was found to be the only predictor of ethical judgment, and moral equity and contractualism were predictors of intent to act. Machiavellianism impacted contractualism, but not relativism. Corporate profit did not affect either ethical judgment or intent to act, and did not interact with Machiavellianism. Implications for business ethics education and training are discussed.